Synthesis and Characterisation of Novel Cyclopenta[c]pyrans Functionalized with Phenothiazine or Terpyridine Units - Crișan, Andreea Petronela; Țepeş, Ana-Maria; Pop, Alexandra Mihaela; Hādade, Niculina Daniela; Bogdan, Elena (Synlett)
This work reports the synthesis and structural characterization of novel derivatives incorporating the cyclopenta[c]pyran core and either a phenothiazine or a 2,2’:6’,2”-terpyridine unit. The coupling between the cyclopenta[c]pyran moiety and the heterocyclic unit was achieved through Suzuki-Miyaura cross-coupling reaction. The compounds were analysed by NMR, UV–vis and fluorescence spectroscopy, while the molecular structure of the phenylcyclopenta[c]pyranyl-biphenylterpyridine derivative, was confirmed by single-crystal X-ray diffraction.